School, multiliteracies and tecnologies in the portuguese language class: reflections from a project on youtubers - Gabriela da Silva Bulla; Mariana Bulegon da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This paper aims at reflecting on school, multiliteracies and technologies in contemporary society. To this end, we describe and analyze a learning project carried out with a ninth grade class in Portuguese Language classes at a public school in Porto Alegre, Brazil. The project focused on multimodal discourse genres such as Youtuber video and written dissertation. We highlight the importance of working with the promotion of multiliteracies in the school that is committed to the formation of citizens that are able to circulate critically through the cybercultural and mediatic spheres inherent in the network society.